Sexualidade saudável: prevenção das infecções sexualmente transmissíveis em estratégias de saúde da família - Lacerda, Tuany Chiappa de (2023)
Sexuality in old age is still characterized as a delicate subject with a complex approach, resulting in the difficulty of promoting the health of the elderly in order to provide a better quality of life and well-being and a matter of preventing sexually transmitted infections (STIs). ). The objective of the study was to analyze the rapid testing of sexually transmitted infections in the elderly in the family health strategies of a city in Rio Grande do Sul. The method used was a document analysis of the monthly reports issued by the Family Health Strategy with data from rapid STI testing in the elderly from 2020 to April 2023. In the end, 153 rapid STI tests were analyzed in people over 60 years. It was noticed with the study that the main factor associated with the transmission of STIs in the elderly is the lack of information on the part of this public and health professionals, associated with cultural aspects and prejudices established by Brazilian society, from Rio Grande do Sul. It is concluded that cultural aspects and misinformation about sexuality in old age contribute to unsafe sexual practices and to the increase in transmission of STIs in the elderly. For this reason, it is necessary that public policies, especially in primary health care, include the elderly public in the creation of health strategies, prevention and promotion of safe and healthy sexual practices.